Unlocking Consumer Growth in Marketplaces: The Power of Artificial Intelligence Marketing and Human Resources Excellence - Arianto, Nurmin; Sunarsi, Denok; Hamsinah, Hamsinah; Kasmad, Kasmad; Asmalah, Lia (International Journal of Artificial Intelligence Research, 2024)
This study aims to analyze the influence of artificial intelligence (AI)-based marketing, the quality of human resources (HR) operating it, and the effectiveness of the marketplace platform on increasing the number of consumers. In the digital era, AI is increasingly used in marketing strategies to personalize customer experiences, increase efficiency, and reach target markets more accurately. However, the role of HR operating AI technology is also crucial in determining the success of implementing this strategy. This study uses a quantitative method with an approach (SEM-PLS) to test the causal relationship between these variables. The research sample consists of business actors on marketplace platforms and online shops that use AI technology in their marketing. The results of the study indicate that AI-based online marketing does not have a significant influence on marketplace development, with a t-statistic value of 1.359 which is smaller than the t table of 1.983 and a P-value of 0.175 which is greater than 0.05. This indicates that even though AI is applied in marketing, its impact on marketplace development is still limited. On the other hand, the quality of human resources also does not have a significant effect on the marketplace, as indicated by the same t-statistic value, which is 1.359, which is smaller than the t table and the P-value exceeding the significance limit of 0.05. This indicates that the quality of human resources in marketplace organizations may need to be focused more on the technological aspect to support better development. On the other hand, the increase in consumers is proven to have a positive and significant effect on the development of the marketplace, with a t-statistic value of 3.212 which is greater than the t table of 1.983 and a P-value of 0.001 which is smaller than 0.05. This finding indicates that the increasing number of consumers can be a key factor for the success of the marketplace in Indonesia.